A prospective observational study conducted in tertiary teaching hospital of Uttar Pradesh to compare safety and efficacy of PPIUCD and interval IUCD (380A) - Gupta, Nidhi; ., Akanksha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of this study was to compare the efficacy and safety of PPIUCD and interval IUCD. Methods: This was a prospective observational study conducted on women attending the OPD and indoor services of S.N. Medical college, Agra. 800 women willing for PPIUCD insertion were included in the study after informed consent excluding chorioamnionitis, PROM>18 hours, unresolved PPH and puerperal sepsis. Another 200 willing women were inserted interval IUCD according to MEC criteria of WHO. All were followed up for 1 year. Results: It was found that rate of expulsion was more in PPIUCD group compared to interval IUCD group (6%vs 1.5% p value <.05),rate of removal was almost similar in both groups (11.5%inPPIUCD and 14%in interval IUCD group), cause of removal was mainly social in PPIUCD group while bleeding was more in interval IUCD group compared to PPIUCD (85.7%vs26%). Conclusions: Postpartum insertion of IUCD is a safe effective, feasible and reversible method of contraception.